Adoption of soil and water conservation technologies in an upland community in Impasug-ong, Bukidnon, Philippines - Pulhin, Juan M.; Rondal, Jose D.; Quiton, Jovelyn D.; Tapia, Maricel A. (2002)
As enacted through Republic Act 8435, better known as the Agriculture and Fisheries Modernization Act (AFMA) of 1997, the modernization of the agriculture and fisheries sectors promotes the use of approriate technologies that would protect the environment, reduce production cost, and increase the global competitiveness of farmers. Hence, the adoption of soil and water conversation and other farming technologies is critical to the success of AFMA. Previous studies suggest that the socioeconomic and related factors that influenced the farmers' adoption of soil and water conservation technologies in Barangay La Fortuna, Impasugong, Bukidnon, Philippines.

Through discriminant analysis, the socioeconomic factors were determined to differentiate the adopters and non-adopters of soil and water conservation technologies. Total land owned, total cost of labor before planting, level of awareness of farmers, and the number of agronomic and organic support technologies practiced were found to be highly associated with the adoption of soil and water conservation technologies. Because several underlying factors were found to influence these variables, the study suggested a holistic approach in delineating adopters from non-adopters.